2020
DOI: 10.1109/access.2020.2973917
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Alleged Gender-Differences in Pedestrian Dynamics: A Study Reveals No Gender Differences in Pedestrian Movement Behavior

Abstract: Pedestrian dynamics are affected by several factors including pedestrian compositions. In this article, we examine the movement characteristics of Palestinian pedestrians using the fundamental diagram for single-file movement experiments conducted with an emphasis on gender compositions. Our findings show that the mean velocity of exclusively male pedestrians is approximately the same as exclusively female pedestrians. For instance, when the number of pedestrians is 20, the velocities for male and female are 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Therefore, Ghanaians require a smaller personal space zone, enabling them to travel quicker than a similar density of German pedestrians and African students in China. The following information has been discovered by experiments on how locations/cultural factors have impacted pedestrians' movement behaviour: it has previously been believed that women move differently from men due to their cultural backgrounds [ 32 ]. However, this research could not verify this assumption in the study because the focus was on the locations and cultural impacts; although males and females displayed similar features, the study needed help digging deep into it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Ghanaians require a smaller personal space zone, enabling them to travel quicker than a similar density of German pedestrians and African students in China. The following information has been discovered by experiments on how locations/cultural factors have impacted pedestrians' movement behaviour: it has previously been believed that women move differently from men due to their cultural backgrounds [ 32 ]. However, this research could not verify this assumption in the study because the focus was on the locations and cultural impacts; although males and females displayed similar features, the study needed help digging deep into it.…”
Section: Discussionmentioning
confidence: 99%
“…The study kept other comparable factors in evaluating the influence of geographical location and culture. The research compared India and Germany [ 2 ] with about the same density and Germany and Palestine with just about the same density, taking into account the differences in pedestrian dynamics based on the composition of the groups [ 32 ]. One noticed that the pedestrians were arranged systematically during Ghanaian experiments and African students in China.…”
Section: Location/cultural Differences In Speed–density Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…A special representation of the fundamental diagram is the speed distance function equation (3.2), including the model parameters v 0 the desired speed, T the slope factor and l the minimal distance between agents. Experimental studies on the fundamental diagram have shown that they depend on a set of individual properties P = {P 1 , P 2 , …} of pedestrians like culture, body height, gender, or motivation [32][33][34][35][36][37]. However, they also depend on various environmental factors E = {E 1 , E 2 , …} like the width of the facility, the presence of rhythm or background music [38,39] or visibility [40].…”
Section: Model Parameters and Psychological Factorsmentioning
confidence: 99%
“…The study found that pedestrians who have a higher motivation have a stronger ability to adapt their velocities. In addition, the topic of gender influence is discussed by Subaih et al [17] and Dias et al [18]. Subaih et al [17] found that the mean velocity of exclusively male pedestrians is approximately the same as exclusively female pedestrians, thus there is no gender difference in pedestrian movement behavior.…”
Section: Introductionmentioning
confidence: 99%